Supplementary Book of Green Consumerism: An Innovation of Environmental Learning based on HOTS - Ichsan, Ilmi Zajuli; Sigit, Diana Vivanti; Miarsyah, Mieke (Universitas Islam Negeri Raden Intan Lampung, 2019)
Learning in the 21st-century, students are required to have a good understanding of the latest environmental issues, namely the ability of Higher-Order Thinking Skills (HOTS). Environmental learning at the Junior High School level in public school and Islamic-based schools requires deepening of the material by the latest environmental issues such as green consumerism. The purpose of this study was to develop an Android-based Supplementary Book of Green Consumerism (SBGC) for environmental learning in natural science subjects. The research method used in this study was the research and development of Borg and Gall development with a few modifications. This study was only carried out up to the validation stage by experts. The results showed that the SBGC was highly valid with a validation score of 3.70 and the percentage of completeness of 92.50 %. Based on the scores obtained, it can be concluded that SBGC is suitable to be used in environmental learning. SBGC has the advantage of being based on technology, based on HOTS, as well as simple and attractive. It can be concluded that SBGC can be used in environmental learning at schools.